(untitled) (The Gaze: Journal of Tourism and Hospitality, 2018)
The paper is essentially related with the study of marketing of a destination. A destination which includes every provision for the visitors attracts continuous flow of visitors. Being a foremost religious site of the Buddhism, the study of Lumbini is always been a subject of choice. In the context of tourism destination marketing, the author engages in a field survey with 184 visitors to gather information on attractiveness and positioning of destination Lumbini; and evaluates the effects with the use of different data analysis methods and statistical tools so as to come to the prospects, challenges and future policy suggestions. The Gaze: Journal of Tourism and Hospitality Vol.9 2018 p.69-82